Contesting Digital Technology through New Forms of Transnational Activism - Edward Webster; Carmen Ludwig (Global Labour Journal, 2023)
While the tech giants are using privatisation to present themselves as providers of solutions to global problems, digitalisation is creating new forms of transnational activism. Global unions are emerging as players in this contest, helping to build counter power at both the local and global level. Through a comparison of the use of digital technology in two case studies in Africa involving two different global unions the article demonstrates how global unions can, through their intermediary coordinating role at the supranational level, deepen worker power.